Entrepreneurship: State of grace or human action? - Carmelo Ferlito (European Journal of Economic and Social Systems, 2015)
Joseph A. Schumpeter developed a very well-known theory of entrepreneurs and entrepreneurship, centred on the concept of `new combinations'. According to him, innovation and entrepreneurship are destructive elements driving the system beyond an equilibrium position and setting in motion a competitive process, in order to reach a new equilibrium point. Though Austrian, Schumpeter was never a member of the Austrian School of Economics. However, his position as regards entrepreneurship is widely commented on by Austrian School members. In particular, Israel M. Kirzner devoted his research activity to develop an alternative concept of entrepreneurship rooted in Misesian human action and the concept of `alertness'. This paper aims to analyze and compare the two positions, in an attempt not so much to stress differences but to find possible common paths for further developments of the concept of entrepreneurship.
Keywords: L26; B53; B13; B25; O31; O33; 330; Entrepreneurship; Schumpeter; Kirzner